Ultimate force and stiffness of 2-piece zirconium dioxide implants with screw-retained monolithic lithium-disilicate reconstructions. Issue 2 (April 2018) - Joda, Tim; Voumard, Benjamin; Zysset, Philippe K.; Brägger, Urs; Ferrari, Marco
Abstract: Purpose: The aims were to analyze stiffness, ultimate force, and failure modes of a 2-piece zirconium dioxide (ZrO2 ) implant system. Methods: Eleven 2-piece ZrO2 implants, each mounted with ZrO2 abutments plus bonded monolithic lithium disilicate (LS2 ) restorations, were grouped for 3.3 mm (A) and 4.1 mm (B) diameter samples. Quasi-static load was monotonically applied under a standardized test set-up (loading configuration according to DIN ISO 14801). The ultimate force was defined as the maximum force that implants are able to carry out until fracture; stiffness was measured as the maximum slope during loading. An unpaired t-test was performed between group A and B for ultimate force and stiffness ( p < 0.05). Results: Force-displacement curves revealed statistically homogenous inner-group results for all samples. Failure modes showed characteristic fractures at the neck configuration of the implants independent of the diameter. Mean stiffness was 1099 N/mm (± 192) for group A, and significantly lower compared to group B with 1630 N/mm (± 274) ( p < 0.01); whereas mean ultimate force was 348 N (± 53) for group A, and significantly increased for group B with 684 N (± 29) ( p < 0.0001). Conclusions: The examined 2-piece ZrO2 implant system mounted to LS2 -restorations seems to be a stable unit under in-vitro conditions with mechanical properties compared to loading capacity of physiological force. The metal-free implant reconstructions demonstrated high stiffness and ultimate force under quasi-static load for single tooth replacement under consideration of the dental indication of narrow and standard diameter implants.